THE DISABLED AND ART: SELECTED ARTIFACTS OF GHANAIAN PHYSICALLY DISABLED ARTISTS AS A RE- SOURCE FOR TEACHING AND LEARNING (Journal of Science and Technology, 2016)
Some disabled artists in Ghana exhibit a lot of rich knowledge and practical skills which are potential materials for teaching and learning. These should be documented otherwise the rich concepts and philosophies inherent in them which, among others, are perceived to depict societal problems may be lost after their death. It is the aim of this paper to identify and document the unique artistic qualities in some of the art works of selected physically disabled artists. It was the pursuit of the writers to contribute to the documentation of these works to serve as resource ma- terial for Art Education and Special Education. Through qualitative research, an enquiry was made into the artifacts of six (6) selected disabled artists in Ashanti Region.  Description of ten (10) works comprising textiles, sculpture, painting, three dimensional (3-D) design, and basketry was done. These physically disabled artists were interviewed using the face-to-face method as data collection instrument. The results of the research largely confirm that the selected artifacts depict problems of the society. Also, a few of the works portray their emotions, personal nature, ideas and philosophy. It is recommended that more physically disabled persons should find life in art since art provides varying types of employment for disabled persons.